2000
DOI: 10.1080/00071660020009225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous supplementations of ascorbic acid, aspirin, vitamin E and selenium on some haematological parameters and serum superoxide dismutase level in broiler chickens

Abstract: 1. This study was conducted using male broiler chickens to determine the effects of ascorbic acid, aspirin, ascorbic acid+aspirin, vitamin E+selenium and ascorbic acid+aspirin+vitamin E+selenium supplementations on haematological parameters and serum superoxide dismutase concentration. 2. One hundred and twenty day-old male Hubbunt broiler chicks were randomly divided into 6 experimental groups of 20 chicks each and placed in different pens. Groups 2, 3, 4, 5 and 6 were given a diet supplemented with ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
7
24
2
2
Order By: Relevance
“…These findings are similar to the findings of Shlosberg et al, (1996) and Tras et al, (2000). Heterophil to lymphocyte (H:L) ratio significantly (P<0.001) decreased in aspirin supplemented birds as compared to control birds at 28 th as well as 42 nd day of age (Table 5 and 6).…”
Section: Resultssupporting
confidence: 80%
“…These findings are similar to the findings of Shlosberg et al, (1996) and Tras et al, (2000). Heterophil to lymphocyte (H:L) ratio significantly (P<0.001) decreased in aspirin supplemented birds as compared to control birds at 28 th as well as 42 nd day of age (Table 5 and 6).…”
Section: Resultssupporting
confidence: 80%
“…Regarding to the effect of Se plus vit E supplementation, our results partially agree with those reported by (Tras et al, 2000;Mohri et al, 2011) who reported that Se and vit E supplementations had no significant effects on haematological parameters such as RBCs, Hb, Ht%, mean corpuscular volume, mean corpuscular haemoglobin concentration and mean corpuscular.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, white blood cell count was increased in lambs given basic diet (P < 0.05). A positive effect of selenium on haematological indicators was observed by several authors (Horton et al 1978;Sehgal et al 1980;Doni et al 1984;L i et al 1990;Chen and Lin 2000;Tras et al 2000), but not confirmed by others (Hu et al 1984;Bednarek et al 1996). Fragility of erythrocyte membranes was significantly decreased in SeO 2 -treated rats compared to control (Chen and Lin 2000).…”
Section: Resultsmentioning
confidence: 79%
“…Fragility of erythrocyte membranes was significantly decreased in SeO 2 -treated rats compared to control (Chen and Lin 2000). However, Tras et al (2000) found that none of the haematological indicators (red blood cell count, haemoglobin, packed cell volume) were affected by a diet supplemented with vitamin E + selenium in male broiler chicken but ascorbic acid + aspirin + vitamin E and selenium supplementation significantly decreased the white blood cell counts.…”
Section: Resultsmentioning
confidence: 99%